Anti-IFNAR treatment does not reverse neuropsychiatric disease in MRL/lpr lupus mice. (November 2019) - Huang, M W; Stock, A D; Mike, E V; Herlitz, L; Kolbeck, R; Putterman, C
Objective: Many systemic lupus erythematosus patients display a type I interferon (IFN) signature, and IFNα levels positively correlate with disease severity. Previous studies blocking the type I IFN pathway systemically in lupus models showed some beneficial effects. However, its effects on neuropsychiatric manifestations have yet to be carefully assessed, even though IFNα has been associated with induction of depression. Our aim was to investigate whether disrupting the type I IFN pathway would attenuate the development of murine neuropsychiatric lupus. Methods: Female MRL/ lpr mice were administered an antitype I IFN receptor (IFNAR) antibody or a control antibody intraperitoneally three times weekly for 12 weeks starting at age 4–5 weeks. Behavior was assessed during and at the end of the treatment schedule. Results: No significant differences were seen between the anti-IFNAR– and control-treated mice when assessing for depression-like behavior or cognitive dysfunction, although anti-IFNAR antibody–treated mice displayed significant decreases in levels of IFN-stimulated genes. Anti-IFNAR treatment also did not significantly improve brain histology, cellular infiltration, or blood-brain barrier integrity. Conclusions: Surprisingly, our results showed no improvement in neuropsychiatric disease and suggest that the role of IFNAR signaling in the pathogenesis of neuropsychiatric lupus continues to need to be carefully assessed.